147k views
1 vote
(X-1)^2 + (y-3)^2=10 convert equation from rectangular form to polar form

User Citronas
by
5.6k points

1 Answer

3 votes

Answer:


r= 2(cos(\theta) + 3sin(\theta))

Explanation:

To convert an equation of rectangular shape to polar form use the following equivalences


x=rcos(\theta)


y=rsin(\theta)


x^2 + y^2=r^2

In this case we have the following equation.


(x-1)^2 + (y-3)^2=10

First we expanded the expression


(x-1)^2 + (y-3)^2=10\\\\(x^2 -2x +1) +(y^2 -6y + 9) = 10\\\\\\x^2 +y^2 -2x -6y = 10-9-1\\\\x^2 +y^2 -2x -6y = 0

Now we know that
x^2 + y^2=r^2,
x=rcos(\theta) and
y=rsin(\theta)

So


r^2 -2rcos(\theta) -6rsin(\theta) = 0\\\\r^2 - 2r(cos(\theta) + 3sin(\theta))=0\\\\r^2 = 2r(cos(\theta) + 3sin(\theta))\\\\r= 2(cos(\theta) + 3sin(\theta))

User Bye
by
5.7k points